Internalizing Moral Responsibility in the Legal Profession through Student Internship Programs: A Study at the Faculty of Sharia, UIN Fatmawati Sukarno Bengkulu - Ilhampatahillah Ilhampatahillah; Alfauzan Amin; Andang Sunarto (Madania: Jurnal Kajian Keislaman, 2026)
This study aims to analyze the internalization of moral responsibility in legal professional ethics through the internship program of students at the Faculty of Sharia, UIN Fatmawati Sukarno Bengkulu. Moral responsibility constitutes an essential element in developing professionalism in the legal field, because legal practice requires technical competence, integrity, and ethical judgment. In legal education, internship programs provide an important space for students to understand, experience, and practice the ethical values of the legal profession in real professional settings. This study employs a descriptive qualitative approach, with data collected through interviews, observation, and document analysis involving internship students, academic supervisors, and institutional mentors. The findings indicate that the implementation of moral responsibility during internship contributes significantly to shaping the professional character of law students, particularly in relation to discipline, integrity, honesty, confidentiality, professionalism, respect for institutional procedures, and concern for justice. The internship experience also encourages students to reflect on the moral consequences of legal services and the importance of protecting the rights of justice seekers. Therefore, internship programs function not only as a medium for practical legal learning but also as a strategic means of instilling moral values and professional ethics as foundations for future legal practice. Penelitian ini bertujuan untuk menganalisis internalisasi tanggung jawab moral dalam etika profesi hukum melalui program magang mahasiswa Fakultas Syariah UIN Fatmawati Sukarno Bengkulu. Tanggung jawab moral merupakan unsur penting dalam pengembangan profesionalisme di bidang hukum karena praktik hukum tidak hanya membutuhkan kompetensi teknis, tetapi juga integritas dan pertimbangan etis. Dalam pendidikan hukum, program magang menyediakan ruang penting bagi mahasiswa untuk memahami, mengalami, dan mempraktikkan nilai-nilai etika profesi hukum dalam lingkungan profesional yang nyata. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan data yang dikumpulkan melalui wawancara, observasi, dan analisis dokumen yang melibatkan mahasiswa magang, dosen pembimbing akademik, dan pembimbing instansi. Temuan penelitian menunjukkan bahwa penerapan tanggung jawab moral selama magang berkontribusi secara signifikan dalam membentuk karakter profesional mahasiswa hukum, khususnya dalam aspek kedisiplinan, integritas, kejujuran, kerahasiaan, profesionalisme, penghormatan terhadap prosedur kelembagaan, dan kepedulian terhadap keadilan. Pengalaman magang juga mendorong mahasiswa untuk merefleksikan konsekuensi moral dari pelayanan hukum serta pentingnya melindungi hak-hak para pencari keadilan. Oleh karena itu, program magang tidak hanya berfungsi sebagai media pembelajaran praktik hukum, tetapi juga sebagai sarana strategis untuk menanamkan nilai-nilai moral dan etika profesi sebagai dasar bagi praktik hukum di masa depan.